Answer: −3x²−15x−30
Step-by-step explanation: use Square of Sum (a+b)²=a²+2ab+b²
−3(x²+2x×3+3²)-3+3x
−(3x² +18x+27)−3+3x
−3x²−18x−27−3+3x
−3x²+(−18x+3x)+(−27−3)
−3x²−15x−30
Hope this helps, now you know the answer and how to do it. Stay healthy and safe and HAVE A BLESSED AND WONDERFUL DAY! :-)
- Cutiepatutie ☺❀❤
Answer:
b = 7/2
x = 11/2
y = 21/2
z = -4
Step-by-step explanation:
2x + 2y + 2z = 24
x + y + z = 12
b + 2x + y + z = 21
2b + 2y = 28
b + y = 14
3x + y + z = 23
we can start anywhere by transforming these equations in a way that always one variable is excised by others.
so, e.g.
b = 14 - y
14 - y + 2x + y + z = 21
2x + z = 7
z = 7 - 2x
3x + y + 7 - 2x = 23
x + y = 16
16 + z = 12
z = -4
-4 = 7 - 2x
-11 = -2x
11 = 2x
x = 11/2
11/2 + y = 16
y = 16 - 11/2 = 32/2 - 11/2 = 21/2
b = 14 - 21/2 = 28/2 - 21/2 = 7/2
Answer:
popcorn=4$
soft drink=4.5$
Step-by-step explanation:
- if we used omitting method:
1-we multiply (p+s=8.5) by (-2) so we could get rid of (s) and be leftover with (p)
so: (-2p-2s= -17)
2- we subtract this equation from (p+2s=13) and the result will be (-p= -4)
3- divide them by (-1) and the result is (p=4)
4-(p+s=8.5) ,substitute (p) with (4) and make it go to the other side with negative sign and the result of (s) is (8.5-4=4.5)
- if we used substituting method:
1-(p+s=8.50), we will make (s) go to the other side with negative sign so the result is (p=8.50-s)
2-(p+2s=13.00), substitute (p) with (8.50-s):
(8.50-s+2s=13)
3- make (8.50) go to the other side with negative sign:
(s=13-8.50=4.5) and then you could get (p)
Step-by-step explanation:
0.5 I think because 5 ÷10 is o.5 but u dont know how much water the tree got.